Dental Pulp Response to Silver-Containing Solutions: A Scoping Review - Ahmed Zaeneldin; Chun-Hung Chu; Ollie Yiru Yu (MDPI AG, 2023)
Dentists used silver-containing solutions for deep cavity disinfection before restoration. This review aims to identify the silver-containing solutions reported in the literature for deep cavity disinfection and summarize their effects on dental pulp. An extensive search was performed using the search words "(silver) AND (dental pulp OR pulp)" in ProQuest, PubMed, SCOPUS, and Web of Science to identify English publications on silver-containing solutions for cavity conditioning. The pulpal response to the included silver-containing solutions was summarized. The initial search identified 4112 publications and 14 publications met the inclusion criteria. Silver fluoride, silver nitrate, silver diamine nitrate, silver diamine fluoride, and nano-silver fluoride were used in deep cavities for antimicrobial purposes. Indirect silver fluoride application induced pulp inflammation and reparative dentine in most cases, and pulp necrosis in some cases. Direct silver nitrate application caused blood clots and a wide inflammatory band in the pulp, whilst indirect silver nitrate application caused hypoplasia in shallow cavities and partial pulp necrosis in deep cavities. Direct silver diamine fluoride application induced pulp necrosis, while indirect silver diamine fluoride application induced a mild inflammatory response and reparative dentine formation. No evidence of the dental pulpal response to silver diamine nitrate or nano-silver fluoride was available in the literature.